Design and Analysis of a Novel Low Complexity and Low Power Ping Lock Arbiter by using EGDI based CMOS Technique - Singh, Sangeeta; Ravindra, JVR; Naik, B Rajendra (International Journal of Integrated Engineering, 2022)
Network-on-chip (NoC) provides solution to overcome the complications of the on-chip interconnect architecture in multi-core systems. It mainly consists of router, links and network interface. An essential component of on-chip router is an arbiter that significantly impacts the performance of the router. The arbiter should provide fast and fair arbitration when it is placed in Critical Path Delay (CPD) systems. The main aim of this research work is to design a novel arbiter for an effective network scheduler in complex real time applications. At the same time resource allocation and power consumption should be very low. Previously, a novel gate level Ping Lock Arbiter (PLA) is designed to overcome the limited fair arbitration in Improved Ping Pong Arbiter (IPPA) with less delay. But the chip size and power consumption are very high. To overcome this problem, an Effective Gate Diffusion Input (EGDI) logic based CMOS scheme is used to design a novel Compact Ping Lock Arbiter (CPLA).  The proposed CPLA is compared with the existing PLA based on static CMOS scheme. The comparison between the conventional and proposed arbiter is carried out to analyze the area, delay and power by using Tanner Tool 14.1 with 250nm and 45nm. The results show that the proposed NPLA achieves low power and consumes less than the existing ping lock arbiter.